Erratum: Role of blood cells in diagnosis of asthma-COPD overlap among patients with COPD - Islam, Md Monimul; Hossain, Md Ali; Bennoor, Kazi Saifuddin; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2020)
Background: As asthma-COPD overlap (ACO) and COPD share some common clinical features, this makes difficult to distinguish them from each other. Since, both of them are characterized by airway inflammation, any inflammatory biomarker such as total count (TC) of white blood cells (WBC), neutrophil, eosinophil and platelet can be used for that purpose. Objective: To assess the role of TC of WBC, neutrophil, eosinophil and platelet in diagnosis of ACO among patients with COPD. Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Dhaka from 2019 March to Feb 2020. In this study, 63 male stable patients (age range: 40 to 80 years) of COPD were enrolled. Among them, 51 patients were finally selected according to exclusion criteria and divided into two groups, ACO (n=26) and COPD alone (n=25). TC of WBC, neutrophil, eosinophil and platelet of all patients were measured by standard lab procedure. For statistical analysis, Chi-Square and Fisher exact test, Shapiro-Wilk test, Mann-Whitney U test were done as applicable. More over, receiver operating characteristic (ROC) curve analysis was performed. Results: In the present study, TC of WBC and neutrophil count were significantly (p<0.01) lower, whereas, blood eosinophil count was significantly (p<0.05) higher in ACO patients than those of COPD-alone. In addition, highest area under the receiver operating characteristic curve was found in case of blood neutrophil count, followed by TC of WBC and eosinophil count. Moreover, at optimal cut off value, the sensitivity, specificity, positive predictive value, negative predictive value of blood count of total WBC were calculated as, 72.00, 61.50, 64.28, 69.56, respectively. However, the aforementioned indices were observed for blood neutrophil count, as 72.00, 76.90, 75.00, 74.07 and for blood eosinophil count, as 38.50%, 92.00%, 83.33%, 58.97%, respectively. Conclusion:The present study reveals that blood count of total WBC, neutrophil and eosinophil, but not the platelet, play substantial role in diagnosis of ACO among the patients with COPD. J Bangladesh Soc Physiol. 2020, December; 15(2): 108-114